2021
DOI: 10.1016/j.xkme.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury in Multiple Myeloma: A Kidney Biopsy Teaching Case

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…15 Patients with IgG type myeloma are prone to a decline in organism immunity, leading to infection and aggravating the disease progression, those with IgA-type are susceptible to hypercalcemia and hypercholesterolemia, while those with IgM and light chain type are prone to renal dysfunction. [16][17][18] It may therefore be of definite value to predict the prognosis of HSCT in patients with multiple myeloma based on the IG type of patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 Patients with IgG type myeloma are prone to a decline in organism immunity, leading to infection and aggravating the disease progression, those with IgA-type are susceptible to hypercalcemia and hypercholesterolemia, while those with IgM and light chain type are prone to renal dysfunction. [16][17][18] It may therefore be of definite value to predict the prognosis of HSCT in patients with multiple myeloma based on the IG type of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the clinical presentation, treatment and outcomes in 20 patients, including ours. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Mean age at diagnosis was 56 years (range, 34 to 82). Patients presented with mean serum creatinine level of 6.7 mg/dL (590 µmol/l), and dialysis was required in 16 (80%).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…7 At the time of diagnosis, almost 50% of the myeloma cases have significantly decreased kidney function (estimated glomerular filtration rate less than 60 mL/minute/1.73m 2 ), with 10 to 15% needing hemodialysis and approximately 1% progressing to end-stage kidney disease. 8,9 A Pakistani research also shows 35% of the myeloma patients had renal impairment (serum creatinine>2 mg/dl) at the time of diagnosis. 5 Studies by Mok et al revealed that chronic kidney disease is positively associated with mortality among myeloma patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Literature has also revealed that improved survival of myeloma patients is linked with reversibility of renal dysfunction. 1,8,10,12 Treatment of myeloma with kidney disease includes removing aggravating factors of renal impairment, drinking enough water, alkalinizing urine, and preventing hypercalcemia as well as hyperuricemia. Dialysis is suitable for myeloma patients with severe renal function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation